Advances and Challenges in Rational Drug Design for SLCs. (October 2019) - Garibsingh, Rachel-Ann A.; Schlessinger, Avner
Abstract : There are over 420 human solute carrier (SLC) transporters from 65 families that are expressed ubiquitously in the body. The SLCs mediate the movement of ions, drugs, and metabolites across membranes and their dysfunction has been associated with a variety of diseases, such as diabetes, cancer, and central nervous system (CNS) disorders. Thus, SLCs are emerging as important targets for therapeutic intervention. Recent technological advances in experimental and computational biology allow better characterization of SLC pharmacology. Here we describe recent approaches to modulate SLC transporter function, with an emphasis on the use of computational approaches and computer-aided drug design (CADD) to study nutrient transporters. Finally, we discuss future perspectives in the rational design of SLC drugs. Highlights: Solute carrier transporters (SLCs) are biomedically important druggable targets but only a few SLCs are targeted by clinically approved drugs. Computer-aided drug design (CADD) has shown promise in the development of tool compounds for SLC transporters. Challenges in CADD for SLCs include the limited number of atomic resolution structures and small-molecule ligands for the development of accurate predictive models. Advances in computational power and machine learning will be powerful in the characterization of SLCs and the design of modulators.